2006
DOI: 10.1269/jrr.0572
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Cytotoxic Activity of Macrophages and Suppressed Tumor Metastases in Mice Irradiated with Low Doses of X- rays

Abstract: We showed in our previous report that a single exposure of mice to 0.1 or 0.2 Gy X-rays led to the significant inhibition of the development of artificial tumor metastases in the lungs and that the effect was related to the enhanced activity of natural killer cells. In the present study, a possible involvement of cytotoxic macrophages in the anti-metastatic effect of the low-level X-ray exposures was investigated. We now demonstrate that irradiation of mice with either of the two low doses of X-rays significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 24 publications
3
36
0
Order By: Relevance
“…injected with 1 ml of 10% Sephadex G-25 (Pharmacia, Uppsala, Sweden) and peritoneal exudate cells were collected on the selected days after cessation of the irradiations (in each case the cells were collected and pooled from at least five mice), resuspended in CM and incubated on glass Petri dishes for 2 h in SC. The glass-adherent cells with morphological features of a typical macrophage were then harvested and resuspended in CM (Nowosielska et al 2006b). …”
Section: Preparation Of Peritoneal Macrophagesmentioning
confidence: 99%
“…injected with 1 ml of 10% Sephadex G-25 (Pharmacia, Uppsala, Sweden) and peritoneal exudate cells were collected on the selected days after cessation of the irradiations (in each case the cells were collected and pooled from at least five mice), resuspended in CM and incubated on glass Petri dishes for 2 h in SC. The glass-adherent cells with morphological features of a typical macrophage were then harvested and resuspended in CM (Nowosielska et al 2006b). …”
Section: Preparation Of Peritoneal Macrophagesmentioning
confidence: 99%
“…injection of mice with carrageenan (CGN -a lysosomedisrupting and phagocyte-damaging compound) (Frank et al 2003) 24 hours before single WBI resulted in the almost total abrogation of the synthesis of NO in the collected peritoneal Mφ regardless of whether the cells were obtained from the irradiated or sham-exposed mice , Nowosielska et al 2006b, 2008). This finding supports a possible involvement of NO in the Mφ-mediated anti-tumor effect of the low-level exposures to X-rays.…”
Section: E M Nowosielska and Othersmentioning
confidence: 99%
“…However, peritoneal Mφ collected from the CGN-treated animals still exhibited cytotoxic activity in vitro, even in the absence of IFN-γ and LPS in the incubation medium. This observation can be explained by triggering of the synthesis of NO in the effector peritoneal Mφ by the target cells (Nowosielska et al 2006b) and/or involvement of other stimulatory mechanisms in the Mφ-mediated function. Indeed, suppression of the activity of the inducible nitric oxide synthase (iNOS) by aminoguanidine (AG -a classical inhibitor of iNOS) markedly reduced the cytolytic function of the effector peritoneal Mφ obtained from both the sham-exposed and irradiated mice (Table 4) (Nowosielska et al 2006b).…”
Section: E M Nowosielska and Othersmentioning
confidence: 99%
“…It is known that an immune system plays an important role in antitumor effects of the low dose ionizing radiation. Several studies demonstrated a reduced lung metastasis in animals irradiated with the low dose radiation (<1 Gy) [7][8][9]. This effect can be associated with an activation of natural killer cells and macrophages, as well as an increased production of cytokines that play an important role in anti-metastatic effects of the ionizing radiation.…”
Section: Introductionmentioning
confidence: 99%